Proteomic analysis of tomato (Lycopersicon esculentum) pollen - Sheoran, Inder S (Journal of experimental botany, 2007)
In flowering plants, pollen grains are produced in the anther and released to the external environment with the primary function of delivering sperm cells to the female gametophyte. This study was conducted to identify proteins in tomato pollen and to analyse their roles in relation to pollen function. Tomato is an important crop which is grown worldwide and is an excellent experimental system. Proteins were extracted from pollen, separated by two-dimensional gel electrophoresis (2-DE), and identified by matrix-assisted laser desorption/ionization-time of flight mass spectrometry (MALDI-TOF MS) and peptide mass fingerprinting. Of the 960 spots observed on Colloidal Coomassie Blue (CCB)-stained 2-DE gels, 190 were selected for analysis. Of these, 158 spots, representing 133 distinct proteins, were identified by searching the NCBInr and Expressed Sequence Tag databases. The identified proteins were classified based on designated functions and the majority included those involved in defence mechanisms, energy conversions, protein synthesis and processing, cytoskeleton formation, Ca(2+) signalling, and as allergens. A number of proteins in tomato pollen were similar to those reported in the pollen of other species; however, several additional proteins with roles in defence mechanisms, metabolic processes, and hormone signalling were identified. The potential roles of the identified proteins in the survival strategy of the small, independent, two-celled pollen grain of tomato, and subsequently in pollen germination and tube growth are discussed